LAM RIAU DALAM DINAMIKA POLITIK RIAU (SEBUAH STUDI SOSIOLOGIS) - Muslim Kazima; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is entitled LAM Riau in the political dynamics of Riau. researchers are interested in taking this theme because LAM Riau is actively involved in the political agendas that occur in Riau. the agendas were Pragmatic, so the substantive agendas of the LAM Riau were questioned. This study also aims to find out how the role of LAM Riau on Riau Malay culture and society and how the influence of Riau's political dynamics on LAM Riau. To answer the existing problems the researcher uses qualitative analysis methods. The data collected is then presented descriptively, namely describing or telling the results of the study with a logical narrative.The results of this study indicate the involvement of LAM Riau in the political dynamics that occurred in Riau. this happened because of the interests of the LAM Riau officials so that the LAM Riau was institutionally carried away by the LAM Riau officials. The lack of innovation in the dissemination of information makes activities that are substantive and directly related to Malay culture make us look at the LAM Riau in vain.Keywords: Role, Political Dynamics, Influence